2014
DOI: 10.1097/prs.0000000000000066
|View full text |Cite
|
Sign up to set email alerts
|

Degeneration, Regeneration, and Cicatrization after Fat Grafting

Abstract: Dynamic remodeling after fat grafting was confirmed. Adipocyte fate differed, depending on the microenvironment: intact survival, replacement with a new adipocyte, or replacement with cicatrization/oil cyst. This detailed understanding will help refine surgical grafting procedures and postoperative evaluation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
91
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 298 publications
(110 citation statements)
references
References 19 publications
5
91
0
5
Order By: Relevance
“…Recent studies by other groups provide strong support for the hypothesis that when fat grafting is successful, this is explained by graft remodelling by stem cells rather than by adipocyte survival (Doi et al, 2015;Dong et al, 2015;Eto et al, 2012;Kato et al, 2014;Zhang et al, 2018). Furthermore, we have reported that the vast majority of grafted adipocytes dies when human fat grafts are implanted in a flow-through chamber model or subcutaneously in the scalp (Tang et al, 2018) in mice and yet new fat growth was seen in each case that was largely host derived.…”
supporting
confidence: 55%
See 3 more Smart Citations
“…Recent studies by other groups provide strong support for the hypothesis that when fat grafting is successful, this is explained by graft remodelling by stem cells rather than by adipocyte survival (Doi et al, 2015;Dong et al, 2015;Eto et al, 2012;Kato et al, 2014;Zhang et al, 2018). Furthermore, we have reported that the vast majority of grafted adipocytes dies when human fat grafts are implanted in a flow-through chamber model or subcutaneously in the scalp (Tang et al, 2018) in mice and yet new fat growth was seen in each case that was largely host derived.…”
supporting
confidence: 55%
“…It is becoming increasingly clear from a number of recent studies that if there is adipocyte survival in grafted fat, this is restricted to the very outermost (100-300 μm) layer (Doi et al, 2015;Dong et al, 2015;Eto et al, 2012;Kato et al, 2014;Tang et al, 2018;Zhang et al, 2018), termed the "survival zone" (Eto et al, 2012). We were unable to identify such a zone in our constructs, and indeed, both adipocytes and adipose-derived stem cells (ASCs; discussed below) throughout the graft showed very poor survival.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations
“…This delay appears to critically impair the survival of the fat cells, which undergo degenerative changes, including the destruction of their nucleus and cell membranes. After this cell destruction, fatty cysts develop and the fat gradually becomes absorbed [25]. Thus, early and abundant neovasculization seems to be the key to the survival of free fat transplants, which in turn leads to good transplant outcomes.…”
Section: Discussionmentioning
confidence: 99%